Global South Doctoral Students and University Employment Services: Personalizing the Relationship (Comparative & International Education Series, 2022)
Recent research recognises the need for Global South students, studying in Global North universities, to develop various sources of capital to enhance employment opportunities aligned with their professional aspirations. As yet however, little attention has been paid to Global South students’ own perceptions in seeking meaningful employment. This book chapter is based on a participative research space which examines this space through exploring the thoughts and feelings of five Global South and three Global North doctoral students within an online research forum. A series of reflective questions are used to question meanings of ‘the Global South’ and ‘employability’ leading to insights into both the Global South experience for doctoral students and their broader employability needs.  We suggest that a shift towards relationship and agency is necessary in order to create an environment whereby Global South students can enhance their employability aligned with their own cultural circumstances.